The Role of Influencer Marketing in Increasing the purchase decision of MSME Products at Shopee - Adinata, Alberta; Sudarmiatin, Sudarmiatin; Wardana, Ludi Wishnu (International Journal of Economics, Business and Innovation Research, 2024)
This study aims to analyze the effect of product quality and marketing through influencers on product purchase decisions on the Shopee platform, by adding a mediating variable in the form of customer trust. The research method used is quantitative with a Smart Partial Least Square (PLS) approach. Data was collected through a questionnaire distributed to 196 respondents, who are active Shopee users. The independent variables in this study are product quality and influencer marketing, the dependent variable is purchase decision, and the mediating variable is customer trust. The analysis shows that product quality and influencer marketing have a significant influence on purchase decision. However, when mediated by customer trust, it is found that customer trust strengthens the relationship between product quality and purchase decision. That is, customer trust in the product makes the impact of product quality on purchase decision stronger. The same is true for influencer marketing, where customer trust in influencer recommendations plays an important role in strengthening their influence on purchasing decisions. The results show that product quality has a greater influence than influencer marketing on purchase decision. However, customer trust serves as an important bridge that connects the two, so companies need to consider how their products and influencer strategies are perceived by consumers in building trust. The implication of this study is the importance of maintaining high product quality and choosing influencers who not only have appeal, but also credibility and can build trust with consumers. This can help increase customer trust, which in turn strengthens purchasing decisions on the Shopee platform.